2017
DOI: 10.1175/bams-d-16-0182.1
|View full text |Cite
|
Sign up to set email alerts
|

The Olympic Mountains Experiment (OLYMPEX)

Abstract: OLYMPEX is a comprehensive field campaign to study how precipitation in Pacific storms is modified by passage over coastal mountains.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
118
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 150 publications
(124 citation statements)
references
References 33 publications
6
118
0
Order By: Relevance
“…Although precipitation processes and instrument challenges (e.g., ground clutter) are different between ocean and land portions of the study domain, this comparison highlights important considerations regarding GPM‐DPR's performance in representing regional precipitation patterns with a relatively short period of accumulated data. There have been several field campaigns and comprehensive validation experiments, such as the Olympic Mountains Experiment (OLYMPEX; Houze et al, ), that have specifically focused on quantifying the performance of GPM‐DPR instrumentation and algorithms in measuring reflectivity and deriving related precipitation products. The comparisons presented here are based on spatiotemporal sampling over multiple seasons and are intended to illustrate how low‐sampling frequency affects subsequent analyses, rather than as an evaluation of instrumentation or algorithm performance.…”
Section: Gpm‐dpr In Situ Validationmentioning
confidence: 75%
See 1 more Smart Citation
“…Although precipitation processes and instrument challenges (e.g., ground clutter) are different between ocean and land portions of the study domain, this comparison highlights important considerations regarding GPM‐DPR's performance in representing regional precipitation patterns with a relatively short period of accumulated data. There have been several field campaigns and comprehensive validation experiments, such as the Olympic Mountains Experiment (OLYMPEX; Houze et al, ), that have specifically focused on quantifying the performance of GPM‐DPR instrumentation and algorithms in measuring reflectivity and deriving related precipitation products. The comparisons presented here are based on spatiotemporal sampling over multiple seasons and are intended to illustrate how low‐sampling frequency affects subsequent analyses, rather than as an evaluation of instrumentation or algorithm performance.…”
Section: Gpm‐dpr In Situ Validationmentioning
confidence: 75%
“…The hypothesis that differences were attributable to sampling deficiency and not measurement or algorithm error is further supported by previous analyses from the OLYMPEX experiment, which demonstrated that airborne instrumentation and algorithms similar to those developed for GPM‐DPR are ideally suited to measure orographic precipitation processes (Houze et al, ). Additionally, GPM‐DPR's predecessor, TRMM‐PR, proved capable of reproducing orographic precipitation gradients in various mountain regions over its lengthy temporal record (e.g., Anders et al, ).…”
Section: Gpm‐dpr In Situ Validationmentioning
confidence: 99%
“…Further, the field of severe thunderstorm research has the potential to provide significant insights, where numerous methods of thermodynamic and debris transport analyses exist, much like how approaches can be borrowed from volcanology (Bodine et al, 2014(Bodine et al, , 2016Broeke & Jauernic, 2014;Snow et al, 1995;Snyder & Ryzhkov, 2015). The adaptation of these methods to wildfire should be informed by targeted field campaigns using various remote sensing platforms (radar and lidar active sensing as well as airborne and spaceborne platforms) with more focus on transition of research to operations (Bluestein, 1999;Houze et al, 2017;Lareau & Clements, 2016;McCarthy et al, 2018). A framework for analysis of wildfire with radar data would be best delivered as science-based tools that meet the unique needs of intelligence gathering for wildfires.…”
Section: Journal Of Geophysical Research: Atmospheresmentioning
confidence: 99%
“…Figure provides one example sampled by ground‐based radar, aircraft, and an overpass of the GPM‐CO. As evident in Figure , orographic perturbation of the prevailing low‐level flow and associated enhancements of the precipitation process were important during OLYMPEX (see also Houze et al ., ; Zagrodnick et al ., ). In fact, Figure b suggests that orographic enhancements occurring below 2 km (Figure c,d) may be difficult to directly observe using GPM DPR observations.…”
Section: Ground Validation Activities and Contributions To The Gpm MImentioning
confidence: 99%